SARCOID IN THE LOWER EYELID DUE TO BOVINE PAPILLOMAVIRUS-2 IN A DONKEY (EQUUS ASINUS) - Eroksuz, Yesari; Abayli, Hasan; Canpolat, Ibrahim; Akdeniz Incili, Canan; Karabulut, Burak; Tanrisever, Murat; Beytut, Enver (Sciendo, 2021)
Sarcoid tumors were described by means of histopathological and molecular procedures in a 5-year-old donkey. Histopathological examination showed epithelial changes including hyperkeratosis, epithelial hyperplasia, koilocytosis, and rete peg formation. Neoplastic fibroblastic cells were plumb, large spindle to stellate and embedded in dense collagenous tissue. Results of Polymerase Chain Reaction and DNA sequence analysis showed that the etiological agent belonged to Bovine Papilloma Virus-II species in the delta papilloma virus genus. This case study represents the first report demonstrating the presence of Bovine Papilloma Virus-II in donkey sarcoid.
Sarkoid donjeg o?nog kapka kod magarca (Equus Asinus) izazvan bovinim papiloma 2 virusom
Keywords: Bovine papillomavirus-2; donkey; Equus asinus; sarcoid